Extraction of Lanthanides(III) along with Thorium(IV) from Chloride Solutions by N, N-di(2-Ethylhexyl)-Diglycolamic Acid. Issue 4 (6th June 2020) - Ibrahim, Sherif M.; Zhang, Yan; Xue, Yun; Yang, Suliang; Ma, Fuqiu; Tian, Guoxin
ABSTRACT: The extraction of Nd(III), Gd(III), and Er(III), which represent light, middle, and heavy lanthanides, respectively, from chloride solutions has been carried out by using N, N -di(2-ethylhexyl)-diglycolamic acid (HDEHDGA, HA) diluted in kerosene as the organic phase. The results from the slope analysis method indicate that the extraction of Ln(III) with HDEHDGA is mainly governed by the cation-exchange reaction mechanisms in the low pH region (pH 1.2–2.7). The obtained data reveal that the extracted species in the organic phase might be LnA3 ∙HA(1 2), which consist of a core of 1:3 LnA3 complex and one additional neutral HA molecule for light Ln(III) or two for heavy Ln(III) associated with the core in the outer coordination sphere. The dependency on the temperatures indicates that the extraction of Ln(III) with HDEHDGA is exothermic and is mainly driven by the exothermic enthalpies crossing the whole Ln(III) series. The extraction of the whole Ln(III) series (except for Pm(III)) and Th(IV) has also been evaluated. HDEHDGA provides remarkable extraction capability with considerable separation factors (SF) for adjacent light Ln(III) pairs (SFCe/La = 6.8, SFPr/Ce = 3.3, SFNd/Pr = 2.5, and SFSm/Nd = 3.5), but relatively poor selectivity for the adjacent heavy Ln(III) pairs. It also presents very good selectivity/extractability for Th(IV) over the light Ln(III) ions (SFTh/La = 1362 and SFTh/Ce = 200). These properties make HDEHDGA a promising extractant for separating Th(IV) from light Ln(III) ions and for separating light Ln(III) ions from each other, which coexist significantly in some Rare Earth (RE) minerals, especially monazite and bastnaesite.